2019
DOI: 10.1159/000496619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Thiol/Disulphide Homeostasis in Children with Nephrotic Syndrome

Abstract: Background: There is a growing body of evidence showing that there is an association between oxidative damage and kidney injury in patients with nephrotic syndrome (NS). Dynamic thiol/disulphide homeostasis (DTDH) is an important antioxidant system. The aim of this study was to determine if DTDH could be used as a biomarker of antioxidant status in pediatric NS patients using a novel automated method. Methods: The study included 39 patients with NS and 40 healthy controls. The DTDH level was measured using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…This hypothesis is supported by the lower albumin levels in children with SSNS and positive correlations between the albumin level and the TT, SH and SS levels. However, the increase in SS/SH and SS/TT ratios in children with SSNS, which are independent of albumin, suggest that TDH shifts towards oxidation in these patients, similar to a previous study 21 . In this context, decreased TT and SH levels in NS patients are not only because of low albumin levels, but also increased oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This hypothesis is supported by the lower albumin levels in children with SSNS and positive correlations between the albumin level and the TT, SH and SS levels. However, the increase in SS/SH and SS/TT ratios in children with SSNS, which are independent of albumin, suggest that TDH shifts towards oxidation in these patients, similar to a previous study 21 . In this context, decreased TT and SH levels in NS patients are not only because of low albumin levels, but also increased oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
“…We found that albumin, TT and SH levels in children with SSNS were lower than in control group. Similarly, Yazılıtaş et al 21 investigated the TDH in children with NS using the new method and found that NS subjects had remarkably lower TT, SH and SS levels when compared with controls. Since albumin makes up the largely portion of the plasma thiol pool, low TT and SH levels can be attributed to low albumin levels in patients with SSNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support other investigations showing increased levels of protein oxidation in patients with NS compared with the control group. 21 , 22 For example, Fan et al 21 found higher levels of advanced oxidation protein products and Yazilitas et al 22 observed increased thiol oxidation in patients with NS than in their corresponding controls.…”
Section: Discussionmentioning
confidence: 99%
“…Bu dengenin klinik uygulamadaki rolünün araştırıldığı bir derlemede 35 çalışma değerlendirilmiş ve tiyol/disülfit dengesinin vücuttaki koruyucu etkisi olduğu ve birçok hastalıkta tanısal belirteç olarak kullanılabileceği belirtilmiştir 8 . Pediatrik yaş grubunda ise tiyol/disülfit dengesinin polikistik over hastalığı 9 , akut tonsillofarenjit 10 , obezite 11 , atopik dermatit 12 , epilepsi 13 , hipotiroidi 14 , bazı metabolik hastalıklar 15 , hipertansiyon 16 , kafa travması 17 , juvenil idiopatik artrit 18 , febril nöbet 19 , akut böbrek hasarı 20 , nefrotik sendrom 21 , Kawasaki hastalığı 22 ve sepsis 23…”
Section: Gi̇ri̇ş Ve Amaçunclassified